Estrogen receptor alpha phosphorylation and its functional impact in human breast cancer. (15th December 2015) - Anbalagan, Muralidharan; Rowan, Brian G.
Abstract: Estrogen receptor α (ERα) is a member of the nuclear receptor superfamily of transcription factors that regulates cell proliferation, differentiation and homeostasis in various tissues. Sustained exposure to estrogen/estradiol (E2) increases the risk of breast, endometrial and ovarian cancers. ERα function is also regulated by phosphorylation through various kinase signaling pathways that will impact various ERα functions including chromatin interaction, coregulator recruitment and gene expression, as well impact breast tumor growth/morphology and breast cancer patient response to endocrine therapy. However, many of the previously characterized ERα phosphorylation sites do not fully explain the impact of receptor phosphorylation on ERα function. This review discusses work from our laboratory toward understanding a role of ERα site-specific phosphorylation in ERα function and breast cancer. The key findings discussed in this review are: (1) the effect of site specific ERα phosphorylation on temporal recruitment of ERα and unique coactivator complexes to specific genes; (2) the impact of stable disruption of ERα S118 and S167 phosphorylation in breast cancer cells on eliciting unique gene expression profiles that culminate in significant effects on breast cancer growth/morphology/migration/invasion; (3) the Src kinase signaling pathway that impacts ERα phosphorylation to alter ERα function; and (4) circadian disruption by light exposure at night leading to elevated ERK1/2 and Src kinase and phosphorylation of ERα, concomitant with tamoxifen resistance in breast tumor models. Results from these studies demonstrate that even changes to single ERα phosphorylation sites can have a profound impact on ERα function in breast cancer. Future work will extend beyond single site phosphorylation analysis toward identification of specific patterns/profiles of ERα phosphorylation under different physiological/pharmacological conditions to understand how common phosphorylation profiles in breast cancer program specific physiological endpoints such as growth, apoptosis, migration/invasion, and endocrine therapy response. Highlights: Identification and initial functional characterization of four novel ERα phosphorylation sites; S46/47, S282, S294, and S559 provides additional understanding of the regulation of ERα signaling. Site specific ERα phosphorylation directs temporal recruitment of ERα and unique coactivator complexes to specific genes. Stable disruption of ERα S118 and S167 phosphorylation in breast cancer cells elicit unique gene expression profiles that culminate in significant effects on breast cancer growth/morphology/migration/invasion. The Src kinase signaling pathway impacts ERα phosphorylation to alter ERα function. Light exposure at night leads to elevated ERK1/2, Src activity and ERα phosphorylation, concomitant with tamoxifen resistance in breast tumor models.